To Determine Frequency of Carotid Stenosis in Patients with Recurrent Stroke - Farheen Khadim, Anwar Ul Haq, Shazia yousaf, Qazi Ikramullah, Fatima Zahra, Ayesha Gull, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine frequency of carotid stenosis in patients with recurrent ischemic stroke by Doppler ultrasound Study design: Cross sectional study Place and Duration: This study is performed at Divisional Headquarter Teaching Hospital, Mirpur AJK from January 2021 to January 2022 Methodology: This study is conducted in sample size of 99 patients, with history of minor stroke or TIA within three month. Now presented with recurrent ischemic stroke .All patients with recurrent ischemic stroke advised carotid Doppler of extracranial carotid arteries. Carotid artery intima media thickness, thrombus, atheromatous plaques and percentage of carotid stenosis and peak systolic flow velocity of affected artery were also determined on Doppler Ultrasound. In addition, association between carotid stenosis and its risk factors such as Age,gender, Hypertension, diabetes ,smoking and dyslipidemia is also determined. Results: We found that 59% of study population with recurrent ischemic stroke have carotid stenosis and percentage of carotid stenosis is variable among study population. Out of 99 patients with recurrent stroke 52% population are Hypertensive, 46% have diabetic, and 58% are smoker and 51% have Dyslipidemia. Conclusion: We concluded that carotid artery stenosis is a risk factor for Recurrent ischemic stroke. It predisposes patients to further attacks of stroke in future .So Doppler Ultrasound must be advised to every patient with history of minor stroke/TIA. So that early intervention should be offered to patients to reduce risk of recurrent ischemic stroke . Keyword: Carotid stenosis, carotid Doppler or Duplex scan ,Stroke /TIA